Long-term oral anticoagulant after catheter ablation for atrial fibrillation. Issue 8 (5th January 2021) - Chew, Derek; Piccini, Jonathan P
Abstract: Catheter ablation is superior to antiarrhythmic therapy for the reduction of symptomatic atrial fibrillation (AF), recurrence, and burden. The possibility of a true 'rhythm' control strategy with catheter ablation has re-opened the debate on rate vs. rhythm control and the subsequent impact on stroke risk. Some observation studies suggest that successful AF catheter ablation and maintenance of sinus rhythm are associated with a decrease in stroke risk, while the CABANA trial had demonstrated no apparent reduction. Other observational studies have demonstrated increased stroke risk when oral anticoagulation (OAC) is discontinued after catheter ablation. When and in whom OAC can be discontinued after ablation will need to be determined in properly conducted randomized control trials. In this review article, we discuss our current understanding of the interactions between AF, stroke, and anticoagulation following catheter ablation. Specifically, we discuss the evidence for the long-term anticoagulation following successful catheter ablation, the potential for OAC discontinuation with restoration of sinus rhythm, and novel approaches to anticoagulation management post-ablation.